2013
DOI: 10.1007/s11250-013-0450-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the treatment of dairy cows at high risk for postpartum metritis and for the treatment of clinical endometritis in Argentina

Abstract: The objectives of this study were to evaluate the efficacy of (1) administering ceftiofur hydrochloride in dairy cows with calving-related disorders to prevent metritis and (2) a combination of GnRH and PGF2α for the treatment of clinical endometritis, under Argentinean dairy farming conditions. Cows at high risk (HRC) for metritis (dystocia, RFM >12 h postpartum, hypocalcaemia, twins, or stillbirth) were randomly assigned to receive either 1.1 mg/Kg of ceftiofur hydrochloride on three consecutive days (HRC tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The former is commonly and extensively used with different veterinary drugs (VD). These VD include antimicrobials (Ceftiofur hydrochloride, oxytetracycline, procaine penicillin G and dihydrostreptomycin, gentamicin, tetracycline hydrochloride and cephapirin) ( Bartolome, Khalloub, de la Sota, Drillich & Melendez, 2014 ; Kasimanickam et al., 2005 ; Okawa et al., 2017 ; Pierre, 2010 , Kumar & Purohit, 2019 , Manimaran et al., 2019 ), non-steroidal anti-inflammatory drug (Phenylbutazone) ( Tek et al., 2010 ); and hormones (Prostaglandins) ( Ahmadi, Mogheiseh, Mirzaei, Nazifi & Fallah, 2018 ; Makki, Ahmadi, Gheisari & Nazifi, 2017 ). In the latter, different phytotherapeutic agents used include Tinosporacordifolia, Withaniasomnifera, Curcuma longa, Ocimum sanctum, Allium sativum, and Azadirachtaindica ( Mandhwani et al., 2017 ; Bakare et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The former is commonly and extensively used with different veterinary drugs (VD). These VD include antimicrobials (Ceftiofur hydrochloride, oxytetracycline, procaine penicillin G and dihydrostreptomycin, gentamicin, tetracycline hydrochloride and cephapirin) ( Bartolome, Khalloub, de la Sota, Drillich & Melendez, 2014 ; Kasimanickam et al., 2005 ; Okawa et al., 2017 ; Pierre, 2010 , Kumar & Purohit, 2019 , Manimaran et al., 2019 ), non-steroidal anti-inflammatory drug (Phenylbutazone) ( Tek et al., 2010 ); and hormones (Prostaglandins) ( Ahmadi, Mogheiseh, Mirzaei, Nazifi & Fallah, 2018 ; Makki, Ahmadi, Gheisari & Nazifi, 2017 ). In the latter, different phytotherapeutic agents used include Tinosporacordifolia, Withaniasomnifera, Curcuma longa, Ocimum sanctum, Allium sativum, and Azadirachtaindica ( Mandhwani et al., 2017 ; Bakare et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Twinning was related with stillbirth in our study, 17.7% of twin calvings had at least one stillborn calf, while only 3.4% of singletons were born dead. It has been shown that cows delivering stillborn D i s c u s s i o n | 124 calves are at higher risk of developing metritis and retained placenta (BARTOLOME et al, 2014;BICALHO et al, 2007a), and this was supported by our data because 48.1% and 11.1%…”
Section: Twinssupporting
confidence: 88%
“…Puerperal metritis (PM) is one of the most common and the cost liest postpartum diseases in dairy cows [1][2] [3]. It reduces fertil ity and milk production [2] [4], and rises treatment cost, discard ed milk costs, and labor costs [2] [4]. Furthermore, PM increases the number of dead or culled cows from the herd during the first 100 days of lactation which is the most profitable period of a dairy cow lactation and therefore increasing replacement costs [2][5] [6].…”
Section: Introductionmentioning
confidence: 99%